Intergrasi Seismik Menggunakan Atribut Seismik dan Amplitude Variation with Frequency (AVF) pada Lapangan Penobscot untuk Mengidentifikasi Fluida pada Tight Sand - purnomo, M Rizki; Erlangga, Mokhammad Puput; Hafizh, Muhammad; Khoirunas, Akhmad (Mataram University, 2025)
This study aims to identify the presence of hydrocarbon-bearing fluids within the tight sand intervals of the Mississauga Formation in the Penobscot Field, Scotia Basin, Canada, through the analysis of amplitude- and frequency-based seismic attributes. The primary dataset comprises 3D seismic volumes processed using Pre-Stack Time Migration (PSTM), supported by well data from Penobscot L-30 and B-41 as lithology and fluid controls. A suite of seismic attributes—including RMS Amplitude, Envelope, Sweetness, Instantaneous Q, Intercept (A), Gradient (B), Low-Frequency Amplitude (15 Hz), and Amplitude Variation with Frequency (AVF)—was computed to evaluate lithological variations and fluid responses within the target interval. Among these, four key attributes—Sweetness, Envelope, Low-Frequency Amplitude (15 Hz), and AVF—were selected for integrated analysis using a multiplicative workflow following data normalization. The integration results reveal pronounced low-frequency (15–25 Hz) amplitude anomalies associated with an anticlinal crest in the central–southern part of the study area. This zone is interpreted as a gas-saturated sandstone layer characterized by low acoustic impedance and significant poroelastic effects. The integrated, normalized multi-attribute approach proves effective in enhancing seismic responses attributable to fluid presence and provides a robust basis for reservoir characterization in unconventional systems, particularly tight-sand environments.